2012
DOI: 10.2138/am.2012.4161
|View full text |Cite
|
Sign up to set email alerts
|

Edgrewite Ca9(SiO4)4F2-hydroxyledgrewite Ca9(SiO4)4(OH)2, a new series of calcium humite-group minerals from altered xenoliths in the ignimbrite of Upper Chegem caldera, Northern Caucasus, Kabardino-Balkaria, Russia

Abstract: Members of the edgrewite Ca 9 (SiO 4 ) 4 F 2 -hydroxyledgrewite Ca 9 (SiO 4 ) 4 (OH) 2 series, structural analogues of clinohumite-hydroxylclinohumite series, Mg 9 (SiO 4 ) 4 (F,OH) 2 , were discovered in xenoliths of carbonate-silicate rock altered to skarn within ignimbrites of the Upper Chegem volcanic structure, Kabardino-Balkaria, Northern Caucasus, Russia. The new minerals occur sparingly in zones containing bultfonteinite, hillebrandite, jennite, and chegemite, as well as rare relics of larnite and rond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Mostly, they are characterized by the presence of wadalite inclusions (Figure 5b). rusinovite, Ca10(Si2O7)3Cl2 [22], pavlovskyite, Ca8(SiO4)2(Si3O10) [23], edgrewite, Ca9(SiO4)4F2 [24], dzhuluite, Ca3SbSnFe 3+ 3O12 [25], etc. More geological information concerning this locality can be found in Gazeev et al [18], Galuskin et al [8,20] and Galuskina et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, they are characterized by the presence of wadalite inclusions (Figure 5b). rusinovite, Ca10(Si2O7)3Cl2 [22], pavlovskyite, Ca8(SiO4)2(Si3O10) [23], edgrewite, Ca9(SiO4)4F2 [24], dzhuluite, Ca3SbSnFe 3+ 3O12 [25], etc. More geological information concerning this locality can be found in Gazeev et al [18], Galuskin et al [8,20] and Galuskina et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…The intensive bands at 607, 636s, and 652 as well as 330, 347w, 413w, and 445 cm −1 can be assigned to the Si-O-Si and O-Si-O asymmetric and symmetric modes of bending vibrations in the [Si 2 O 7 ]-groups. The bands observed in the ranges of 900 to 1000 and 700 to 850 cm −1 can be related to the asymmetric and symmetric vibrations of the same bonds[20,21]. The bands at 481s, 497, 538, 593, 177, and 196 cm −1 are assigned to the bending and stretching vibrations of the Ti-O, Zr-O, Mn-O, and Fe-O bonds in respective cation-centered octahedra [22,23].…”
mentioning
confidence: 99%
“…SEM was applied for visual inspection of surface morphology (texture) and crystalline structure. According Galuskin et al, the natural hydroxyledgrewite mineral showed combinations of pinacoids and rhombic prisms. Meanwhile SEM micrographs of synthetic hydroxyledgrewite showed irregular form particles with average size 2‐6 μm (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxyledgrewite (Ca 9 (SiO 4 ) 4 (OH) 2 ) is dibasic calcium silicate hydrate (C/S‐2.25), and as α‐C 2 SH belong to nesosilicates or orthosilicates group; these silicates possess the lowest degree of polymerization possible, namely CSH phases with isolated silicon tetrahedra (Q0) . Hydroxyledgrewite was first discovered in 2009, approved by CNMNC IMA in March of 2012 and named in honor of Edward S. Grew, a well‐known scientist in the areas of mineralogy and petrology . Galuskin et al also described physical and optical properties, chemical composition and crystal structure of natural edgrewite and hydroxyledgrewite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation